Shariah Monitoring, Agency Cost and Fund Performance in Malaysian Mutual Funds - Sofi, Mohd Fikri; Yahya, Mohamed Hisham (Emerald Group Publishing Limited, 2020)
This paper aims to examine the effect of Shariah Advisory Panel (SAP) on both the level of agency cost and fund performance against conventional corporate governance, within corporate and Shariah governance settings, between Shariah and conventional mutual fund (CMF), in an emerging economy of Malaysia during the period 2008-2015. Panel data regression is appropriately used within corporate governance research because of empirical issues of unobserved heterogeneity effects to avoid spurious evidence. The secondary data of 172 CMFs and 80 Shariah mutual funds are gathered hand-collected from annual reports and master prospectuses for the purpose of analysis between the period 2008 and 2015, generating 2,016 fund-year observations. SAP is found to have a positive effect on agency costs. Consequently, it leads to empirical evidence that substantiates a negative and marginally significant association with fund performance when designated by accounting measure. Thus, the Shariah monitoring proxy is not a good mechanism for controlling agency costs inconsistent with performance maximizing (agency cost minimizing) outcomes. The unique data set of mutual funds used in this research may restrict the generalization of the findings unless mentioned and explained specifically the data characteristics. The single proxy for Shariah monitoring could be better off by having a list of different measures. The paper highlights and suggests a consistent improvement in regulation that could be performed by policymakers pertaining to the non-trivial additional cost of implying Shariah governance. This paper provides empirical evidence of the SAP effects from the view of a more complex monitoring structure in consequence of having an additional layer of governance, devoting on the trade-off between benefit and cost to shareholders